A New Area of Utilizing Industrial Internet of Things in Environmental Monitoring - Lou, Helen H.; Mukherjee, Rajib; Wang, Zhenyu; Olsen, Tim; Diwekar, Urmila; Lin, Sidney (Frontiers in Chemical Engineering, 2022)
Due to environmental regulations continually reducing emission quantity allowed overtime, there is a growing need for adaptable and feasible environmental monitoring; such as emission, wastewater quality, air pollution monitoring, for the process industry (and surrounding communities). Alternative environmental monitoring and process monitoring technologies based on Industrial Internet of Things (IIoT) and Artificial Intelligence (AI) enable the process industry to take a proactive approach towards environment and asset integrity management. The monitoring devices can be deployed in a stationary or dynamic manner. In this paper, the emerging trend and various applications of IIOT and advanced data analytics methodologies in environmental monitoring are reviewed. An example showing challenges and research needs in sensor placement is given. Future direction in technology, regulation and application have been discussed as well.